High-fat diet-induced obesity accelerates puberty in male rats through SMIM20/phoenixin upregulation - Xie, Tao; Qin, Wei; Zeng, Dan; Wang, Runqi; Chen, Shuting; Chen, Yanfei; Zhong, Jingzi; Lan, Dan (Frontiers in Endocrinology, 2025)
BackgroundControversy exists regarding the relationship between obesity and pubertal onset in boys, and the underlying mechanisms remain unclear.ObjectiveTo establish a high-fat diet (HFD)-induced obesity model in juvenile male Sprague-Dawley (SD) rats, and to investigate the relationship between obesity and pubertal advancement as well as the role of Smim20/phoenixin (PNX) in male pubertal development.MethodsA HFD (45% fat) was administered to male SD rats to induce obesity, while control rats were maintained on a normal diet (ND) from birth. Body weight and preputial separation were monitored as markers of obesity and pubertal onset. At prepubertal (postnatal day 30, PND30) and early pubertal (PND40) stages, serum, hypothalamus, pituitary, testes, and adipose tissue were collected. RT-qPCR was performed to measure the mRNA expression levels of key genes in the hypothalamic–pituitary–gonadal axis (HPGA), including gonadotropin-releasing hormone (GnRH), Kiss1, G protein-coupled receptor 54 (GPR54), GnRH receptor (GnRHr), and Smim20. Serum luteinizing hormone (LH), follicle-stimulating hormone (FSH), testosterone, and PNX protein were measured by ELISA. Associations among obesity (body mass index, BMI), PNX, and pubertal timing were evaluated using Spearman’s correlation.ResultsHFD-fed rats exhibited significantly greater body weight and fat mass than ND-fed rats at both time points. (P<0.001), with earlier preputial separation (P<0.001). Testicular weight and expression of GnRH, Kiss1, GPR54, and GnRHr were increased, alongside higher serum LH, FSH, and testosterone (all P<0.05). PNX expression in hypothalamus, pituitary, testes, and subcutaneous fat, as well as serum PNX-14 and PNX-20 levels, were significantly elevated in HFD rats compared with controls (P<0.05). After adjusting for BMI, serum PNX-20 and PNX-14 (P<0.001) remained higher in the HFD group. Body weight was negatively correlated with age at preputial separation and positively correlated with serum LH, testosterone, abdominal circumference, PNX.ConclusionTo our knowledge, this study established a novel HFD–induced model of prepubertal obesity and central precocious puberty (CPP) in male rats. The findings suggest that obesity may accelerate pubertal onset, and that Smim20/PNX may participate in regulating pubertal development in males.